Phenotypic and Molecular Characterization of Bovine Mastitis Milk Origin Bacteria and Linkage of Intramammary Infection With Milk Quality - Huma, Zul I.; Sharma, Neelesh; Kour, Savleen; Lee, Sung Jin (Frontiers in Veterinary Science, 2022)
Mastitis is a multi-etiological complex disease of dairy cows and negatively affects the quality and quantity of milk. Milk is a nutritious food for human being; milk quality is negatively affected by intramammary infection of dairy cows. A total of 300 milk samples were collected from mastitis dairy cows irrespective of parity and stage of lactation, 235 (78.33%) samples were culturally positive and yielded 1,100 bacterial isolates. Staphylococcus aureus was found to be the prime etiological agent involved in the mastitis of dairy cows, followed by Escherichia coli and other environmental pathogens. On the molecular characterization of isolates obtained from the milk culture, various toxic genes such as nuc, seb, hla, stx1, stx2, hly, and Sagl were found on different isolated bacteria. Milk somatic cell counts (SCC) were found to be directly related to the severity of mastitis. On drawing the SCC correlation with milk components, it was found that SCC had a significant negative correlation with fat, lactose, solid not fat (SNF), and ash. It was concluded that mastitis-affected milk contains numerous pathogenic bacteria, toxins, and reduced milk quality, which is unfit for human consumption.